Carotenoid Research in the Food and Nutrition Department, National Health Institute Dr. Ricardo Jorge, Portugal - Dias, Maria da Graça (2017)
The contribution of the Department of Food and Nutrition of the National Institute of Health Dr. Ricardo Jorge (Portugal) to the investigation of carotenoids in Portugal.